Identification of three dietary groups in French university students and their associations with nutritional quality and environmental impact - Arrazat, Laura; Nicklaus, Sophie; de Lauzon-Guillain, Blandine; Marty, Lucile (Frontiers in Nutrition, 2023)
The student period is associated with changes in eating habits, usually leading to diets of lower nutritional quality. However, some variability may exist in students' dietary patterns. We aimed to describe French students' diets and identify dietary groups that may vary in nutritional quality and environmental impact. A representative sample of French students (N=582) for age, sex and scholarship status completed an online 125-item food frequency questionnaire. The nutritional quality of diets was assessed by a score of adherence to the French nutritional guidelines (sPNNS-GS2 score, ranging from -17 to 11.5) and its environmental impact by greenhouse gas emissions for an isocaloric diet (GHGE). An ascending hierarchical classification analysis on food and beverage intakes led to three dietary groups. Between-group differences in food consumption, dietary indicators and sociodemographic characteristics were investigated using ANOVA models. The average sPNNS-GS2 score of students' diets was -0.8 ± 2.8, representing a 57% coverage of French nutritional recommendations, and GHGE were 5.4 ± 1.7 kg eCO2/2000 kcal. The three dietary groups were: a healthy diet group (20% of the sample) with the highest nutritional quality and high GHGE, which included older students with a higher level of physical activity; a Western diet group (40%) with the worst nutritional quality and high GHGE, which included more students who lived with their parents; and a frugal diet group (40%) with the lowest energy intake, intermediate nutritional quality, and low GHGE, which included more students who lived alone. None of the dietary groups optimized both nutritional quality and environmental impact simultaneously, which suggests an apparent incompatibility in the student population between these two sustainability dimensions. These findings emphasize the need for tailored public health policies that acknowledge the diversity of student eating patterns and address specific individual barriers to healthy and sustainable diets. ** "Field of studies" responses grouped together in "Science": "Industry", "Health" and "Sciences" and "Humanities":